Overcoming Financial and Access Barriers in Global Cancer Care With Low-Dose Immunotherapy: A Systematic Review - Celine Hoyek; Binbin Zheng-Lin; Jennah J. Bauernfeind; Omar Hussain Al-Ahmad; Tanios Bekaii-Saab; Sakti Chakrabarti; Sawsan Rashdan; Mohamad B. Sonbol (JCO Global Oncology)
PURPOSEImmune checkpoint inhibitors (ICIs) have significantly improved outcomes in various malignancies. However, the high cost of these therapies limits access for much of the global population. This systematic review aims to evaluate the efficacy of low-dose ICIs compared with standard doses in different malignancies, addressing financial and access barriers in global cancer care.METHODSWe conducted a systematic review of studies comparing the efficacy of low-dose versus standard-dose ICI regimens in advanced solid tumors. A comprehensive search was performed across multiple electronic databases, including retrospective and prospective studies. Excluded were animal studies, editorials, conference papers, book chapters, and other immunotherapy modalities. Outcomes assessed included overall survival (OS), progression-free survival, and objective response rate. Results were summarized descriptively due to study heterogeneity.RESULTSFrom 1,010 screened articles, four studies with 435 Asian patients were included, covering a variety of solid tumors. All included studies were with a low quality of evidence and a high risk of bias due to retrospective design. Two studies used weight-based dosing (pembrolizumab <2 mg/kg and nivolumab <2.15 mg/kg), showing similar OS to standard dosing in non–small cell lung cancer (NSCLC) and renal cell carcinoma, respectively. Flat dose regimens in two studies (nivolumab 20 mg or 100 mg once every 3 weeks and pembrolizumab 100 mg once every 3 weeks) also demonstrated comparable OS in NSCLC.CONCLUSIONLow-dose ICIs may offer equivalent clinical benefits to standard dosing, potentially reducing costs and expanding access in developing countries. Although awaiting more representative randomized clinical trials, weight-based ICI regimens could be a viable alternative in low- and middle-income countries.